Problem-Based Learning in Aqidah and Akhlaq Education at MTs Muhammadiyah 04 Blagung - Heru Purwo Yulianto; Mujiburrohman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the implementation of problem-based learning (PBL) in Aqidah and Akhlaq education as an instructional approach to address students’ learning and moral development challenges at MTs Muhammadiyah 04 Blagung. The purpose of this research is to analyze how problem-based learning is designed and applied in Aqidah and Akhlaq instruction, to identify the types of student problems addressed through this approach, and to explore its impact on students’ understanding, attitudes, and moral behavior. The main research questions focus on: (1) how problem-based learning is implemented in Aqidah and Akhlaq education, (2) what learning and moral problems are encountered by students, and (3) how problem-based learning contributes to the development of students’ cognitive, affective, and behavioral dimensions.This study employs a qualitative research design using a case study approach. Data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis of lesson plans and learning materials. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through triangulation of sources and methods. The findings indicate that problem-based learning in Aqidah and Akhlaq education encourages active student engagement, critical thinking, and reflective moral reasoning. Students demonstrate improved understanding of Islamic values, increased responsibility in addressing real-life moral problems, and more positive behavioral changes. The study concludes that problem-based learning is an effective pedagogical strategy for integrating cognitive understanding and moral practice in Aqidah and Akhlaq education, and it offers meaningful implications for the development of innovative Islamic education learning models